Numerical analysis of crimping and inflation process of balloon‐expandable coronary stent using implicit solution. (31st May 2017) - Bukala, Jakub; Kwiatkowski, Piotr; Malachowski, Jerzy
Abstract: The paper presents an applied methodology for numerical finite element analysis of coronary stent crimping and the free inflation process with the use of a folded noncompliant angioplasty balloon. The use of an implicit scheme is considered as the most original part of the work, as an explicit finite element procedure is very often preferred. Hitherto, when the implicit solution was used for the finite element solution, the simulated issue was largely simplified. Therefore, the authors focused on the modelling methodology with minimum possible simplification, ie, a full load path (compression and inflation in single analysis), solid element discretization, and sophisticated contact models (bodies with highly different stiffness). The obtained results are partially compared with experimental data (radial force during the crimping procedure) and present satisfactory compliance. The authors believe that presented methodology allow for significant improvement of the obtained results, as well as potential extension of the research scope, compared to previous efforts performed using the explicit integration scheme. Moreover, the presented methodology is believed to be suitable for sensitivity and optimization studies. Abstract : This paper presents an applied methodology for numerical finite element analysis of coronary stent crimping and the free inflation process with the use of an implicit scheme for numerical finite element analysis. Presented methodology is focused on modelling with minimum possible simplification, ie, a full load path, solid element discretization, and sophisticated contact models. The authors believe that presented methodology allows for significant improvement of the obtained results compared to previous efforts.